Parity, Imprecise Comparability and the Repugnant Conclusion. (22nd April 2016) - Chang, Ruth
Abstract : This article explores the main similarities and differences between Derek Parfit's notion of imprecise comparability and a related notion I have proposed of parity . I argue that the main difference between imprecise comparability and parity can be understood by reference to 'the standard view'. The standard view claims that 1) differences between cardinally ranked items can always be measured by a scale of units of the relevant value, and 2) all rankings proceed in terms of the trichotomy of 'better than', 'worse than', and 'equally good'. Imprecise comparability, which can be understood in terms of the more familiar notions of cardinality and incommensurability, rejects only the first claim while parity rejects both claims of the standard view. I then argue that insofar as those attracted to imprecise comparability assume that all rankings are trichotomous, as Parfit appears to, the view should be rejected. This is because imprecise equality is not a form of equality but is a sui generis 'fourth' basic way in which items can be ranked. We should, I argue, understand imprecise equality as parity, and imprecise comparability as entailing 'tetrachotomy' – that if two items are comparable, one must better than, worse than, equal to, or on a par with the other. Thus those attracted to the idea that cardinality can be imprecise should abandon trichotomy and accept parity and tetrachotomy instead. Finally, I illustrate the difference between Parfit's trichotomous notion of imprecise comparability and parity by examining how each notion might be employed in different solutions to the problem posed by the Repugnant Conclusion in population ethics. I suggest that parity provides the arguably more ecumenical solution to the problem.